The THE DIFFERENCE OF PHYSICAL DIMENSION IN THE QUALITY OF LIVING ON PATIENTS OF DIABETES MELLITUS BETWEEN GIVING HYPERBARIC OXYGEN THERAPY 10 DAYS AND 5 DAYS - mufarika mufarika; Siti Aminah (Bina Sehat Press. Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2018)
ABSTRACT Quality of life is the subjective perception of the individual to the physical, psychological, social, and environmental conditions experienced. The aim of the study was to analyze differences in the physical dimensions of the quality of life of diabetes mellitus patients between providing hyperbaric oxygen therapy 10 days and 5 days. This study used the quasy experiment method with the approach of pre post test with control group design. The population in the study was 882 people with a sample of 14 respondents divided into two groups. 7 respondents in the treatment group and 7 respondents in the control group. Sampling used was consecutive sampling technique. Data were analyzed using Paired t test and Independent t test. The results of the Paired t test statistic in the treatment group had differences in quality of life before and after 10 days of hyperbaric oxygen therapy, while the control group had no difference in quality of life before and after 5 days of hyperbaric oxygen therapy. The independent t test results were different after being given hyperbaric oxygen therapy 10 days and 5 days. It is expected that health workers can be used as a reference source and as a basis for determining nursing intervention in the management of diabetes, especially in the quality of life of diabetic patients.